Edukasi Literasi Keamanan Data Pribadi dan Mitigasi Social Engineering bagi Siswa SMAN 7 Kecamatan Cikokol Kota Tangerang - Slamet, Try Setyo; Tsamratul’ain, Annisa (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
The rapid digital transformation in urban areas like Tangerang City has increased the risk of cybercrime, particularly social engineering techniques targeting adolescents. Students at SMAN 7 Tangerang are active social media users but often possess low personal data security literacy. This Community Service (PKM) activity aims to enhance students’ awareness and mitigation capabilities against psychological manipulation threats in cyberspace. The implementation method involved interactive workshops including identification stages, education based on phishing attack simulations, and evaluation using pre-tests and post-tests. The results indicated a significant increase in student understanding, with the average attack identification score rising by 52% following the training. Students are now able to implement practical protection steps, such as enabling Two-Factor Authentication (2FA) and recognizing suspicious communication patterns. This program proves that behavior-based education is effective in fostering a cyber-aware culture within the school environment to minimize the risk of personal data theft.